Enhanced effect of radiofrequency ablation on HCC by siRNA-PD-L1-endostatin Co-expression plasmid delivered - Pengfei Chen; Kun Li; Jinwei Chen; He Hei; Jiaxin Geng; Nannan Huang; Mengyu Lei; Huijie Jia; Jianzhuang Ren; Chenwang Jin (Translational Oncology)
Hepatocellular carcinoma (HCC) poses a significant clinical challenge due to high mortality and limited treatment options. Radiofrequency ablation (RFA) is commonly used but can be limited by tumor recurrence. This study explores the potential of combining RFA with an attenuated Salmonella strain carrying siRNA-PD-L1 and endostatin to enhance HCC treatment. In this study, an H22 subcutaneous tumor mouse model was used, with animals divided into five groups for treatment with a blank control, a blank Salmonella plasmid, RFA alone, siRNA-PD-L1-endostatin, or a combination of RFA and siRNA-PD-L1-endostatin. The combination therapy significantly reduced tumor growth, angiogenesis, and PD-L1/VEGF expression in tumor tissues post-RFA. Additionally, it induced tumor cell apoptosis, inhibited proliferation and migration, and increased the infiltration of T lymphocytes, granzyme B+ T cells, and CD86+macrophages within tumors. There was also a notable rise in T and NK cell populations in the spleen. In conclusion, combining RFA with siRNA-PD-L1-endostatin delivered by attenuated Salmonella synergistically enhances anti-tumor effects, boosts the anti-tumor immune response, and improves RFA efficacy for HCC.